The impact of erlotinib use in non-small-cell lung cancer patients treated in a private reference general hospital and in a private cancer clinic from 2005 to 2011 - Bognar,Cinthia Leite Frizzera Borges (2015)
ABSTRACT Objective: To report the demographic data and clinical outcomes of non-small-cell lung cancer patients exposed to erlotinib in any line of treatment. Methods: This was a retrospective cohort study of nonsmall-cell lung cancer patients from a reference general hospital and a private oncology clinic, who received erlotinib from 2005 to 2011. Statistical analysis was performed and we evaluated demographic data and response to treatment, by correlating the results of this first cohort published in Brazil with results of current literature. Results: A total of 44 patients were included; 65.9% were diagnosed with adenocarcinoma, and 63.6% had metastatic disease. The mean age was 63.3 years. The median follow-up was 47.9 months. Epidermal growth factor receptor mutation screening was performed in 22.7% of patients (n=10), with mutation present in 30% of patients. The median overall survival was 46.3 months, and there was a higher probability of survival at 60 months for females compared to males (29.4% versus 15.8%; p=0.042). The other variables did not present significant statistical difference. Conclusion: We collected the largest cohort of patients with non-small-cell lung cancer who have used erlotinib in Brazil to date, and demonstrated that outcomes of patients treated at our clinic during the study period were consistent with the results of current literature in similar patients.